The influence of the residual copper on the pipes steel hot plasticity according to environmental requirements - Rusănescu C.O.; Rusănescu M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Considering the importance of gaseous and/or liquid fuels impact on the environment, the resistance of pipelines at hot plastic deformation is important. Therefore, in order to avoid or reduce any adverse impact on the environment, the influence of residual copper on hot deformability of steel pipes was investigated in this paper. The negative copper influence was experimentally proved using torsion deformation at temperatures above 1000o, under the air and argon atmosphere. The samples were heated and then deformed at different temperatures with constant deformation rate. Also, structural analysis of investigated materials was done, using metallographic and SEM analysis.